The effects of external and internal focus of attention on motor learning and promoting learner's focus - Ghorbani Saeed; Dana Amir; Fallah Zynalabedin (Sciendo, 2019)
Study aim: External focus of attention is considered as a critical factor in the OPTIMAL theory of motor learning. This theory proposes that external focus of attention facilitates motor performance and learning because it promotes focusing on the task goal. However, the effects of external focus of attention on focusing on the task goal are not well understood. The aim of this study was, therefore, to investigate the effects of an external focus of attention versus an internal focus of attention on motor learning and promoting focus of the learner on the task goal.